(3jJjejI GdYUQ aj HjGf SHH GdeO hGdLRQs - (3YHO GdbGOQ Hf CMeO Hf Ydj Hf ejejs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdeGA CeG HYO ajbhd YHO GdbGOQ Hf CMeO Hf Ydi GHf ejei cGf Gddg dg ai LejY MGdGJg ChdkG ef HjGf SHH GdeO hGdLRQ s
(3BNQgG (B:s
(3hefgG JfTC GdcQGeGJ GdHGgQI Ndb Gddg ef gPg GdSeGA edGFcI djS dge YHGOI EdG EQTGO GdNdb Edi CfhGQ GdMb GfJgi JeJ GdQSGdI GdehSheI HhQi GdRfO HGdLRQ hGdeO hEf TFJ bd jJjejg GdYUQ ai GdeO hGdLRQ hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B731s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdLZQGajG h GdHdOGfs